Relevance Of National Education Policies As An Effort To Improve The Quality Of Madrasah Tsanawiyah Education Services - Najib Kusnanto; Agus Sukristyanto; Achluddin Ibnu Rochim (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
The quality of educational services is the most important part of the administration of the management of educational institutions, especially in madrasah which are religion-based institutions. This study aims to describe efforts to improve the quality of education services, and explore constraints to quality improvement and find a model for improving the quality of madrasah education by considering the relevance of national education policies. This study uses a descriptive qualitative method with a case study approach that chooses the object of the public tsanawiyah madrasah in Surabaya. The data was collected through interviews and FGDs as well as documents on student development. The results of the study can explain that the management of madrasah institutions since the implementation of the 2013 curriculum until now has not indicated an increase in the quality of aspects of education services, especially quality that can be measured from outcomes or graduation. Madrasah management must still be motivated by trying to raise awareness from those involved in management. Internal factors that become obstacles in fulfilling the SNP are (1) educational staff, (2) leadership support, (3) infrastructure, (4) availability of funds, and (5) understanding of the school community regarding the implementation of the SNP. While the external factors that are thought to be hindering the fulfillment of the SNP are (1) the geographical location of the school, (2) the carrying capacity of the community, and (3) the economic conditions of the surrounding community. The model for improving the quality of education services in madrasah is directed at service synergy, which integrates the school management administration system and the quality control cycle. With regard to this synergy, it is suggested that local governments issue regulations governing quality assurance in madrasah schools by involving the Office of Education and the Ministry of Religion which oversees the Madrasah system and curriculum to jointly develop measurable and sustainable indicators of improving the quality of Madrasah education services.